Бежин луг и другие рассказы - Тургенев Иван Сергеевич (Внеклассное чтение, 2016)
Экземпляры: (20190806) / Инвентарный номер: 5240 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 87 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6